Upaya Mahasiswa Kesejahteraan Sosial USU Dalam Meningkatkan Kepercayaan Diri Seorang Anak Di Rumah Pintar YAFSI - Yosep Lorenzo Panjaitan , Nicolas; Utama Ritonga , Fajar (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2024)
Children who live their daily lives playing with their peers, whether at school, playgrounds and learning, home, will increase their self-confidence. Confidence in terms of being able to interact, express their opinions and communicate well, express positive affirmations for themselves and their peers, and be able to determine a decision. This child's confidence will be needed until they grow up, and will increase the child's sense of independence. However, in carrying out the Social Welfare Field Work Practice at the YAFSI Smart House, the author found cases of individual children, who did not believe in the abilities possessed by these individuals. So that the author provides assistance and facilitates the individual child to be able to develop themselves, and be able to increase self-confidence, through providing a role that the individual will be responsible for. With the role given, it aims for the individual child to be able to start determining their own decisions slowly, and be able to express what they feel, thus further improving communication skills, and increasing the individual child's self-confidence.